Safety and effectiveness of escitalopram in an 8-week open study in Chinese patients with depression and anxiety - Wang G (Dove Medical Press, 2018)
Gang Wang,1 Xiumin You,2 Xueyi Wang,3 Xiufeng Xu,4 Ludong Bai,5 Jian Xie,6 Zhijian Yao,7 QiZhong Yi,8 Jun Ma,9 Jinan Wang,10 Jianmin Zhuo,11 Cuili Hu11 1Psychiatry Department, Beijing Anding Hospital, Capital Medical University, National Clinical Research Center for Mental Disorders, Beijing, China; 2Psychiatry Department, Xianyue Hospital, Xiamen, China; 3Psychiatry Department, Institute of Mental Health of Hebei Medical University, Shijiazhuang, China; 4Psychiatry Department, Kunming Medical University Affiliated Hospital, Kunming, China; 5Psychiatry Department, Shangdong Province Mental Hospital, Jinan, China; 6Psychiatry Department, Hangzhou First People Hospital, Hangzhou, China; 7Psychiatry Department, Nanjing Brain Hospital, Nanjing, China; 8Psychiatry Department, Xinjiang University Affiliated First Hospital, Urumqi, China; 9Psychiatry Department, Inner Mongolia Mental Hospital, Hulun Buir, China; 10Medical Department, Lundbeck Pharmaceutical Information Consulting Co., Ltd., Beijing, China; 11Medical Department, Xi’an Janssen Pharmaceutical Ltd., Beijing, China Background: Anxiety symptoms usually worsen depression and functional impairment. The present study was aimed to evaluate the impact of escitalopram on social function and quality of life in major depressive disorder (MDD) patients with anxiety symptoms. Patients and methods: Adult MDD patients with functional impairment (Sheehan Disability Scale [SDS] score ≥9) and anxiety symptoms (Hamilton Anxiety Rating Scale [HAM-A] score ≥14) received escitalopram (10–20 mg/day) for 8 weeks. Symptom status was assessed by SDS, Quality of Life Enjoyment and Satisfaction Questionnaire-Short Form, Montgomery-Åsberg Depression Rating Scale (MADRS), HAM-A, and Quick Inventory of Depressive Symptomatology-Self Report scales. Safety was evaluated by treatment-emergent adverse events (TEAEs). Results: Overall, 208 (79.7%) of 261 enrolled patients completed the 8-week treatment. Mean (SD) SDS and Quality of Life Enjoyment and Satisfaction Questionnaire-Short Form total scores were 17.4 (5.87) and 39.3 (14.43) at baseline, which improved to 7.6 (6.71) and 61.6 (15.80), respectively, at week 8. Totally, 59.2% of patients achieved functional remission (SDS≤6) and 61.7% of patients achieved depression remission (MADRS≤10) at week 8; 48.1% of patients achieved both functional and depression remission (SDS≤6 and MADRS≤10). The change in SDS total score was positively correlated with the change in MADRS and HAM-A total scores at each visit. Patient’s baseline SDS score was related with depression score (regression coefficient=0.40582, p=0.0005); remission of SDS was statistically related to a reduction of week 2 and week 6 HAM-A score (p<0.0001) and reduction of MADRS score (p<0.0001). Overall, 25.7% of patients reported ≥1 TEAEs. Most frequently reported TEAEs were nausea (5.8%), diarrhea (2.3%), and dizziness (2.7%). Most TEAEs were mild to moderate in severity. Four patients reported serious TEAEs, two patients reported suicide attempts, and one patient completed suicide. Conclusion: Escitalopram (10–20 mg/day) treatment was efficacious in reducing depression, improving social function, and quality of life in MDD patients with anxiety symptoms. No new safety signals were identified. Keywords: anxiety, Chinese, escitalopram, major depressive disorder, social function